PENGARUH KETIDAKPUASAN KONSUMEN, KARAKTERISTIK KATEGORI PRODUK, DAN KEBUTUHAN MENCARI VARIASI TERHADAP KEPUTUSAN PERPINDAHAN MEREK - Junaidi, Shellyana; Dharmmesta, Basu Swastha (Journal of Indonesian Economy and Business, 2002)
The objective of this study is to examine the partial and simultaneous effects of customer dissatisfaction, characteristics of product category, and variety-seeking needs on brand switching behavior. This study has tested the impact of the variety-seeking needs as a moderating variable on brand switching behavior and provided an alternative perspective on the concept of consumersâ brand loyalty. The brand switching approach can be very helpful in resolving problem and decision making related to brand loyalty reinforcement. The results show two important findings. Firstly, the customer dissatisfaction and variety-seeking needs were significantly related to brand switching behavior, but the impact of characteristics of product category itself on brand switching behavior was not significant. Secondly, the variety-seeking needs moderated the effects of customer dissatisfaction and characteristics of product category on brand switching behaviors. Some implications for future research are identified, including the choice of products as research objects, dissatisfaction constructs, and the importance of inter-customer interaction issues.Key words: brand switching, customer dissatisfaction, characteristic products, variety-seeking, involvement